Mike Mignola's Hellboy universe the secret histories - Mignola, Michael 1960-; Arcudi, John; Mitten, Chris (Dark Horse Books, 2021)
"When did Rasputin find his calling to bring about Ragna Rok? How did the Visitor stay hidden on Earth for so long? And where did the legendary Sledgehammer armor really come from? These questions and more are answered in this new collection from the world of Hellboy! Three stories of instrumental side characters are explored in full, collected for the first time in a handsome hardcover perfect for any Hellboy fan's library"--